Analysis Of Footwork Ability In Badminton Games For Children Aged 10 – 12 Years At Yanti Jaya Badminton Club - Hasyim Hasyim; M. Irfan Hasanuddin (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine the ability of footwork in badminton games for children aged 10-12 years at the Yanti Jaya Badminton Club. The type of research used in this research is descriptive quantitative research. Quantitative descriptive analysis is used to collect, summarize and interpret the data obtained, which is then reprocessed so that it is expected to produce a clear, holistic picture of the problem that is the object of research. The population in this study were 20 members of the Yanti Jaya badminton club. The sample used was 20 people using a sampling technique, namely Saturated Sampling (census). The results of the study obtained the proportion of the effects of the ability to walk from 20 people or (100%); the results of the excellent category were four people or (20%); the moderate type was 14 people or (70%), and the poor class was two people or (10 % ). Thus, the ability to footwork in badminton games for children aged 10-12 years at the Yanti Jaya badminton club is in the moderate category with a proportion of 70%. This proves that the analysis of footwork ability at the Yanti Jaya badminton club is already good and needs to be improved again to achieve more on the badminton sports field.